KAJIAN KONTRIBUSI INVESTASI INFRASTRUKTUR JALAN TERHADAP PEREKONOMIAN WILAYAH DITINJAU DARI SEKTOR TRANSPORTASI BARANG - Anas, Ridwan; Tamin, Ofyar Z.; Wibowo, Sony Sulaksono (FSTPT Indonesia, 2015)
The transport sector can not be separated from the economic sector, in which the role of transport as a logistics that will affect the production sector. The high cost of transportation will increase production costs and result in a lack of competitiveness of economic sectors in Indonesia (the Foundation and LPEM-UI, 2008). This study tried to describe the contribution of road infrastructure investment to Gross Domestic Product (GDP) in terms of the transportation cost. The role of infrastructure investment is a way to lower the cost of transportation of goods and increase communication among the connected region, the road infrastructure investment will improve the performance of road transport as this will affect the production sector identified areas affected by the reduction in cost of production of economic sectors can be quantified as a value-added GDP measured in region.